The synthesis and characterization of 1,2-O-cyclohexylidene-4-aza-8-aminooctane and some of its transition metal complexes - Sekerci, M; Tas, E (John Wiley & Sons Inc, 2000)
1,2-O-Cyclohexylidene-4-aza-8-aminooctane (L) has been synthesized stavting from 1-chloro-2,3-O-cyclohexylidene which has been prepared by the reaction of epichlorohydrin with cyclohexanone. The complexes of this ligand with Co(II), Ni(II), Cu(II), and UO2(VI) salts were prepared. The structures of the ligand and its complexes are proposed based on elemental analyses, IR, UV-vis, H-1, and C-13 NMR spectra, magnetic susceptibility measurements thermogravimetric analyses, and differential thermal analyses. (C) 2000 John Wiley & Sons, Inc.
Keywords: Dioxouranium(Vi) Complexes; Nickel(Ii); Palladium(Ii); Platinum(Ii); Copper(Ii); Cobalt(Ii); Polymers; Oximes; Acid